Application of Direct Instruction Learning Model to Improve Student Learning Outcomes on Basic Competencies Implementing Wood Construction Work Procedures at SMK Negeri 1 Lotu for the 2022/2023 Academic Year - Perista Zalukhu; Aprianus Telaumbanua (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The problem in this study is that the Direct Instruction learning model has not been optimally applied to the Basic Competency of Implementing Wood Construction Work Procedures and student learning outcomes are limited to achieving KKM, namely 70. Research objectives: (1) To describe the learning process by applying the Direct Instruction learning model to Basic Competency Implementing Wood Construction Work Procedures at Lotu 1 State Vocational High School for the 2022/2023 Academic Year, and (2) To find out student learning outcomes in the Basic Competency of Applying Wood Construction Work Procedures at Lotu 1 State Vocational School for the 2022/2023 Academic Year. This type of research is Classroom Action Research (CAR). This research was conducted at SMK Negeri 1 Lotu with research subjects of class X-DPIB students, totaling 22 students. The instruments in this study were observation sheets of the learning process (teacher respondents), observation sheets of student activity, photo documentation, and practical activity tests. With the data analysis technique, namely the observation sheet is processed with a Likert scale and the learning achievement test is carried out by a practical activity test. The results of the study: (1) In the first cycle, the average percentage of observations in the learning process (teacher respondents) was 73.21%, the average percentage of observations of student activity was 48.44%, the average calculated learning outcomes was 66.57 with a percentage of student completeness of 45% and this result has not reached the target that has been set, namely 70. (2) While in cycle II (two) the average percentage of observations in the learning process (teacher respondents) is 85.71%, the average percentage observation of student activity is 83.10%, the average student learning outcomes is 83.10 which is categorized as good with a complete percentage of student learning outcomes of 100% and has reached the set target of 70. From the research findings above it can be concluded that by applying the Direct Instruction learning model in the Basics of Building Construction and Soil Measurement Techniques Basic Competency of Applying Wood Construction Work Procedures can improve student learning outcomes at SMK Negeri 1 Lotu.